Validation of intraosseous delivery of valproic acid in a swine model of polytrauma. Issue 1 (17th March 2021) - Biesterveld, Ben E; O'Connell, Rachel; Kemp, Michael T; Wakam, Glenn K; Williams, Aaron M; Pai, Manjunath P; Alam, Hasan B
Abstract : Background: Intraosseous (IO) drug delivery may be necessary in emergency situations when intravenous access is unattainable. Valproic acid (VPA) is a histone deacetylase inhibitor that has previously been shown to improve survival in preclinical models of lethal polytrauma. In this study, we sought to compare serum levels of intravenously and IO-delivered VPA, and to analyze the effect of IO-delivered VPA. Methods: Swine were subjected to 40% blood volume hemorrhage, brain injury, femur fracture, rectus crush injury and liver laceration. After 1 hour of shock, animals were randomized (n=3/group) to receive normal saline resuscitation (control), normal saline+intravenous VPA 150 mg/kg (intravenous group) or normal saline +IO VPA 150 mg/kg (IO group). Serum levels of VPA were assessed between groups, and proteomics analyses were performed on IO and control groups on heart, lung and liver samples. Results: Intravenous and IO serum VPA levels were similar at 1, 3, 5 and 7 hours after starting the infusion (p>0.05). IO-delivered VPA induced significant proteomics changes in the heart, lung and liver, which were most pronounced in the lung. Biologic processes affected included inflammation, metabolism and transcriptional & translational machinery. The control group had 0% survival, and the intravenous and IO group both had 100% survival to the end of the experiment (p<0.05). Discussion: IO-delivered VPA is noninferior to intravenous administration and is a viable option in emergent situations when intravenous access is unattainable. Level of evidence: Not applicable (animal study).